Nasal Reconstruction with Paramedian Forehead Flaps at University of Port Harcourt Teaching Hospital and Professor Kelsey Harrison’s Hospital, Port Harcourt, South-South, Nigeria: Our Experience - Akunekwe, M. I.; Gbeneol, T. J. (British Journal of Healthcare and Medical Research, 2022)
Background: Nasal reconstruction is one of the most challenging head and neck surgeries. It demands a thorough understanding of the anatomy of the nose by the surgeon who will do a meticulous planning and have an excellent surgical skill in order to achieve good outcomes. The forehead flap is a veritable option for reconstruction with acceptable colour match and donor site morbidity. In our environment, the skill is not yet readily available. Objective: To share our experience with the use of paramedian forehead flap in the reconstruction of complex defect of the nose in the two referral hospitals in the South-South zone of Nigeria. Method: This is a retrospective study which involved analysis of the data obtained from the three male patients treated in two referral hospitals from the month of May 2013 to April 2015. Three cases of nasal defects reconstructed with paramedian forehead flaps were presented. The three cases designated 1, 2 and 3 here, presented with full thickness defects of varying number of aesthetic subunits, resulting from matchete cut, high velocity gunshot and human bite respectively. In all the cases, the three-dimensional form of the nose was achieved, with patent nasal passage which was indeed a pretty challenge. The outcome, including the donor site morbidity, was acceptable to all the patients, so were satisfied. Result: The complex defects, involving the lining, the skeletal support and the cover, in the three male patients were reconstructed using paramedian forehead flap, and both lining and skeletal support were provided. The outcome in terms of the colour match, texture, patency and tip projection were acceptable to the patients. Conclusion: Paramedian forehead flap remain the workhorse for nasal reconstruction and the expertise is available in the Port Harcourt to serve the populace in the South-South region of Nigeria.